Between Secularisation and Loss of Faith - Dobra, Dorin Mircea (Chrześcijaństwo-Świat-Polityka, 2024)
We study the thesis that today we are faced with secularization in its true sense, and not so much with the loss of faith. At a summative and sentimental look, it would seem that faith in God is losing ground among the masses. The desecration of more and more religious edifices, or their simple depopulation, creates an image that confirms the thesis of contemporary society's distance from the Church. But we seek to evaluate how much of our behaviour today is actually deeply Christian in a secularized Europe.